Dipole moment derivatives of hydrogen cyanide - Kim, K.; Kim, N. (1994)
An ab initio quantum-mechanical calculation was done in order to analyse the dipole-moment derivatives in hydrogen cyanide (HCN). The computed integrated infrared intensities, atomic polar tensors, atom anisotropies, and effective atomic charges were compared with the corresponding experimental values. For the stretching modes of HCN, the explicit inclusion of electron correlation was necessary to bring the calculated values in line with the experimental data. To describe the bending mode correctly, polarization and diffuse functions had to be included in the basis set. With regard to the charge-charge flux-overlap analysis, both the charge flux and overlap contributions seem to play an important role in the atomic polar tensors of the carbon and nitrogen atoms; these must be included if the calculated results are to agree, at least in sign, with the experimental results. ？ 1994.